Trisomy 18 syndrome with cleft foot. Issue 8 (August 1988) - Castle, D; Bernstein, R
Abstract : Ectrodactyly of the feet has been reported only twice in association with trisomy 18 syndrome. A severe form of this anomaly, the first with published illustrative x rays, is described in a male infant with trisomy 18 syndrome. It is suggested that this may represent an extreme expression of the foot anomalies more commonly associated with this syndrome.